Evidence on Efficacy and Safety of Chinese Medicines Combined Western Medicines Treatment for Breast Cancer With Endocrine Therapy - Li, Lu; Wang, Rongyun; Zhang, Aolin; Wang, Ling; Ge, Qianwen; Liu, Yuan; Chen, Tianhui; Wang, Chi Chiu; Leung, Ping Chung; Sun, Qiuhua; Fan, Xiaohui (Frontiers in Oncology, 2021)
Background: Endocrine therapy is commonly applied and important as a treatment for breast cancer, but it usually induced a variety of side effects. Chinese Medicines (CM) has been proven therapeutically effective on reducing adverse effects caused by endocrine therapy in many clinical studies. But strong evidence is still limited on the efficacy and safety of CM combined western medicines treatment (CM-WM) for breast cancer. Objective: To systematically study the efficacy and safety of CM-WM as an adjuvant treatment for reducing side effects induced by endocrine therapy in breast cancer patients. Method: We searched relevant clinical studies in databases up to February 28, 2021 and only included Randomized Controlled Trials (RCTs). We extracted data from these included RCTs, assessed study quality, conducted meta-analyses by RevMan 5.4 and applied pooled Risk Ratios (RR) or Mean Difference (MD) with 95% CIs in the meta-analyses. Results: Totally 28 trials involving 1926 participants were included for our systematic review. 6 RCTs compared CM-WM with CM placebo-WM, while 22 RCTs compared CM-WM with WM alone. No studies compared CM-WM with no treatment. The meta-analysis results shown that compared with CM placebo-WM treatment, CM-WM treatment could significantly improve the quality of life (P=0.02). The meta-analysis results also shown that compared with WM treatment alone, CM-WM treatment could significantly improve the bone mineral density (P<0.0001), TCM syndrome score (P=0.0002), Kupperman scales (P<0.0001), KPS scales (P=0.0005) and the quality of life (P=0.003), while significantly relieve pain (P<0.0001). Compared with WM, incidences of TCM symptoms (nausea, vomiting, fatigure, etc) (P<0.0001) were decreased significantly by CM-WM. As to safety assessment, serum calcium concentration, estradiol, ALP, CD3, CD4 and CD8 counts, no significant differences were found between the two treatments (P>0.05). Serious side effects or reactions were not reported in all included studies. Conclusion: This systematic review preliminarily suggested that CM-WM treatment is therapeutically effective and safe on breast cancer patients. The adjunctive use of CM may reduce the endocrine therapy associated adverse events, including decreased bone mineral density, reduced perimenopausal symptoms and impaired immune function. But more large-scale RCTs with higher quality are needed to support the application of CM-WM therapy.